Application of Belgian endive (Cichorium intybus var. foliosum) dietary fiber concentrate to improve nutritional value and functional properties of plant-based burgers. (August 2022) - Twarogowska, Anna; Van Droogenbroeck, Bart; Fraeye, Ilse
Abstract: Increasing consumer awareness of health and climate is being reflected in their dietary choices. This is reflected in the strong growth in the market for plant-based food, with plant-based burgers (PBB) being the most popular meat alternative. PBB must be based on natural ingredients that increase nutritional value, improve technological properties, and create satisfying physical sensations. Fibers obtained from agri-food by-products can potentially meet all of these requirements. The dietary fiber concentrate (DFC) produced from the forced roots of Belgian endive ( Cichorium intybus var. foliosum ) (by-product) has shown potential for application in PBB. Replacing soy protein with 5% and 10% of DFC from Belgian endive (DFC-BE) resulted in lower caloric value and sugar content and doubled dietary fiber concentration in the end product, enough to justify a "high fiber" nutrition claim (>6 g per 100 g). Baking properties such as baking yield, moisture retention, and dimeter reduction also improved. Application of DFC-BE can also be used to regulate pH, color, texture profile, and sensory attributes. Individual recipes must be adjusted to obtain the required results. Highlights: Dietary fiber concentrate from Belgian endive (DFC-BE) forced roots was used as an functional ingredient. DFC-BE replaced soy proteins at the level of 5 and 10% in plant-based burgers formulation. The addition of DFC-BE lowers the caloric value and increases dietary fiber content in the end product. The baking properties were improved after the addition of the DFC into the formulation. Application of DFC-BE can be used to regulate pH, color, texture profile, and sensory attributes.